Perancangan Aplikasi Pembelajaran Dasar Bahasa Jepang Berbasis Android Dengan Implementasi Algoritma Fisher-Yates Shuffle - Reyca Liani Chandra; Beny Beny; Agus Nugroho (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
The ability of a foreign language is a distinct advantage for an individual. One of the most popular foreign languages is Japanese. Based on a questionnaire that has been conducted to 44 respondents, 65.9% have an interest in learning Japanese for various reasons. Then 93.8% stated that the Japanese language learning media was not enough. This application contains basic Japanese material such as katakana, hiragana, kanji, and grammar material that is equipped with questions that can be done by the user. This application is made by implementing the Fisher-Yates Shuffle algorithm which is used to randomize the questions contained in this application. So that users can work on questions repeatedly.